2020
DOI: 10.1002/ejic.202000148
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Reactivity of Monoguanidinate Rare‐Earth Metal Aminobenzyl Enolate Complexes

Abstract: Two monoguanidinate rare‐earth metal aminobenzyl enolate complexes LRE(CH2C6H4NMe2‐o)(OCH=CH2)(THF) (L = (PhCH2)2NC(NC6H3iPr2‐2,6)2; RE = Y (1a), Lu (1b)) were synthesized via two pathways of the ring‐opening of THF, and their reactivities with some molecules were also explored. Reaction of complex 1a with iPrNCNiPr gave the insertion product LY[(NiPr2)2CCH2C6H4NMe2‐o](OCH=CH2)(THF) (2). Whereas, in the case of PhNCS, LY[SC(CH2C6H4NMe2‐o)NPh](OCH=CH2)(THF) (3) and the ligands redistribution binuclear yttrium e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 121 publications
0
3
0
Order By: Relevance
“…20 e ,21 Only two non-Cp analogues were documented. 22 Treatment of 1 with HPPh 2 (2 equiv.) in THF at 70 °C for 72 h could also yield complex 6 (84%) directly (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…20 e ,21 Only two non-Cp analogues were documented. 22 Treatment of 1 with HPPh 2 (2 equiv.) in THF at 70 °C for 72 h could also yield complex 6 (84%) directly (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…, [La­(Bn) 2 (THF) 4 ]­[BPh 4 ] ( 255 ), [La­(Bn Me ) 2 (THF) 4 ]­[BPh 4 ], [La­(Bn)­(THF) 6 ]­[BPh 4 ] 2 ( 256 ), and [La­(Bn Me )­(THF) 6 ]­[BPh 4 ] 2 (Scheme ). These starting materials can also be used to generate heteroleptic alkyl complexes with bidentate nitrogen donors, such as amidinates ( 257 ), guanidinates ( 258-RE ; RE = Y, La, Dy, Lu), , and ferrocenyl bis- amides ( 259-RE ; RE = Nd, Gd, Ho, Er) (Scheme ). …”
Section: Organometallic Reagentsmentioning
confidence: 99%
“…guanidinates (258-RE; RE = Y, La, Dy, Lu),682,683 and ferrocenyl bis-amides (259-RE; RE = Nd, Gd, Ho, Er) (Scheme 73) 339. Furthermore, RE benzyls can be employed to generate new organometallic complexes.Harder first showed that 245-RE can deprotonate HCp BIG (Cp BIG = {C 5 Ar 5 } − ; Ar = C 6 H 4 R-4; R = Et, i Pr, n Bu) to afford the heteroleptic Cp derivatives [RE(Cp BIG )-(Bn NMe2 ) 2 ] (260-RE; RE = Y, Nd, Dy, Tm).…”
mentioning
confidence: 99%